Knowledge Management di Era Digital dan Kecerdasan Buatan: Tinjauan Sistematis Literatur 2025–2026 - Suci Putri Lestari; Kusuma Agdhi Rahwana; Evilia Sri Yuniar (JURNAL EKONOMI PERJUANGAN, 2026)
This study presents a systematic literature review (SLR) examining the development of knowledge management (KM) research based on a bibliometric analysis of 500 Scopus-indexed articles from 2025–2026. Using thematic and bibliometric analysis methods, the literature was grouped into ten thematic clusters. Results show that KM Systems & Practices (68 articles), Knowledge Sharing & Transfer (54 articles), and Education & Learning (53 articles) are the largest themes, while AI & Generative AI (43 articles) is the fastest-growing theme — increasing 107% from 2025 to 2026. Key findings include: (1) a paradigm shift from traditional SECI models toward AI-based KM frameworks; (2) growing integration of KM with sustainability (ESG) agendas; (3) significant research gaps in developing country contexts, public sector organizations, and SMEs. This article provides a comprehensive roadmap for KM researchers and practitioners